The NGOisation of Education - (:unkn) unknown (My University, 2012)
Based on insights from the West African country Benin, this thesis studies the processes of the NGOisation of education from an empirical perspective. It focuses on four case studies, namely 1. the Primary Education Teacher's Training Programme carried out by the INGO IFESH;2. Aide et Action's installation of a Municipal Education Committee in Nikki; 3. the Education First Project against child trafficking conceptualised by World Education, Terre des Hommes and the Catholic Relief Services; and 4. a project for self-managed school canteens run by the Catholic Relief Services. The projects' analyses are grounded in ten months of multi-sited field research in Nikki, Karimama, Parakou, Cotonou and Porto Novo.
Keywords: African Research